2005
DOI: 10.1158/1541-7786.mcr-05-0022
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylations of DEAD Box p68 RNA Helicase Are Associated with Cancer Development and Cell Proliferation

Abstract: The nuclear p68 RNA helicase is essential for normal cell growth. The protein plays a very important role in early organ development and maturation. In our previous report, we showed that recombinant p68 RNA helicase was phosphorylated at serine/threonine and tyrosine residue(s). In the present study, we examined the phosphorylation status of p68 in six different cancer cell lines and compared the results with those in cells derived from the corresponding normal tissues. We showed here that p68 was phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 40 publications
1
89
0
1
Order By: Relevance
“…In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005). Therefore, different cellular signaling pathways activated in different cellular contexts may favor one of the molecular functions of ddx5 and ddx17, which could have different impact on cell behavior and tumor progression.…”
Section: Ip Flagmentioning
confidence: 99%
“…In this context, several reports have indicated that the splicing and transcriptional activities of ddx5 and ddx17 can be modulated by different post-translational modifications that depend on cellular signaling pathways (Yang et al, 2006(Yang et al, , 2007Jacobs et al, 2007;Carter et al, 2010;Mooney et al, 2010a, b). In addition, several post-translational modifications of ddx5 or ddx17 have been shown to be altered in different cancers (Causevic et al, 2001;Yang et al, 2005). Therefore, different cellular signaling pathways activated in different cellular contexts may favor one of the molecular functions of ddx5 and ddx17, which could have different impact on cell behavior and tumor progression.…”
Section: Ip Flagmentioning
confidence: 99%
“…Besides their role in RNA biogenesis there is now evidence to indicate that DEAD box RNA helicases can participate in the progression of cancer (Abdelhaleem, 2005). For example, human DDX5 has been shown to be overexpressed at the protein level in colorectal tumors as well as in the hepatic tumor cell lines, HT-29 and HCT116, which have undergone an epithelial-mesenchymal transition (Yang et al, 2005(Yang et al, , 2006. In addition, DDX5 has been shown to upregulate the expression of cyclin D1 along with c-myc genes, which promoted cell proliferation in a series of mammalian cell lines (Yang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we previously demonstrated that platelet-derived growth factor (PDGF) or EGF stimulation led to tyrosine phosphorylation of p68 RNA helicase in SW480 cells (16,19). Presently, our experiments demonstrated that binding to tyrosine phosphoprotein converted PKM2 from tetramer to dimer and therefore activated the protein kinase activity.…”
Section: Resultsmentioning
confidence: 64%
“…Nevertheless, an actual tyrosine-phosphorylated cellular protein that interacts with PKM2 was not identified and demonstrated. We previously showed that p68 RNA helicase is phosphorylated at tyrosine residues in cancer cells, and tyrosine phosphorylation of p68 correlates with cancer progression (16). Phosphorylation of p68 at Tyr-593 promotes epithelial-mesenchymal transition (14), whereas phosphorylation of p68 at Tyr-593 and Tyr-595 mediated resistance to apoptotic induction (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation